Study on Dynamic Characteristics and Energy Consumption Characteristics of Ultra-supercritical Units Operating at Wide-Load - Xiaoyang Hu; Baihui Liu; Zheng Jing; Binbin Qiu; Zhu Wang; Jingshi Wang; Junjie Yan (Chemical Engineering Transactions)
With the increasing integration of renewable energy generation into the power grid, coal-fired power plants are compelled to engage in deep load regulation. The dynamic characteristics and energy consumption of coal-fired units operating at ultra-low loads have emerged as significant concerns. In this study, a dynamic simulation model for the wide-load operation of a 1,000 MW ultra-supercritical coal-fired unit was established using GSE software. The model can simulate the operational process of the unit within the load range of 150-1,000 MW. This study initially analyses the dynamic characteristics of the unit load-up process, taking the intervals of 150-320 MW and 830-1,000 MW as examples. Subsequently, a comparative analysis is conducted on the energy consumption levels under different intervals and load-up rates. The results indicate that during the load-up process, 260 MW is the turning point at which the water wall operation state transitions from wet to dry. Under a load-up rate of 5 MW/min, as the load interval gradually increases, the total coal supply during the load-up process increases from 66.08 t to 195.83 t. Within the range of 830-1,000 MW, when the load-up rate rises from 5 MW/min to 15 MW/min, the total coal supply throughout this process decreases from 195.83 t to 67.86 t. This established model holds significance for optimizing energy consumption levels during wide-load operation processes of units by providing insights into their dynamic behaviour under varying loads.